Hand hygiene, its learning through the use of teaching aids - Zenia Tamara Sánchez García; Yuliett Mora Pérez; María de los Ángeles Villegas; Carmen Damilsy Sevajanes Pérez; Annia Iglesias Armenteros; Yuliemy Basso Mora (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2023)
Background: improving hand hygiene in an effective and sustained way is achieved through the application of multiple measures to address different obstacles, as well as behavioral barriers, and then it is necessary to create teaching aids that allow their learning. Objective: to design teaching aids that contribute to the learning of hand hygiene both in nursing students and in the community. Methods: a qualitative-quantitative research was carried from June 2018 to July 2021. The selected settings were the Marineritos del Sur Children's Care Center, Guerrillero Heroico Elementary School and the Cienfuegos University of Medical Sciences. Discussion groups were held in the three scenarios, from which the categories training and teaching aids emerged, which were created and validated by the Barraza methodology. Results: a web page, a mobile application, educational games for children and triptychs were designed. All were successfully validated. Conclusions: the design of teaching aids, scientifically supported, corresponds to the needs of the Nursing Bachelor's degree students and the community for the achievement of theoretical and practical knowledge in adherence to the correct hand hygiene technique.